How to make a billion in 9 steps - Harpin, Richard (Piatkus, 2025)
'Richard is the real deal. No fluff, no BS . . . just clear, actionable insights and an easy-to-follow blueprint for success. If you don't believe simple steps can deliver a business worth billions, read this, and then think again.' JAKE HUMPHREY, author of High Performance___________________________________________________________Richard Harpin became an entrepreneur at the age of just seven when he started selling conkers to his school friends. Fifty years later he sold a company he founded, HomeServe, for over £4 billion.In How to Make a Billion in Nine Steps, Harpin shares the lessons he learned along the way, and the things he wishes he had known that could have got him to a billion-pound valuation faster.He reveals his uncomplicated, grounded and honest approach to business, showing that start-up success is not rocket science. And he shares his practical wisdom for building a company from the ground up, identifying opportunities, creating effective marketing, planning for future growth, hiring brilliant people and developing the key qualities of a great leader.It will inspire a new generation of CEOs, fitting them for a world of ever-evolving challenges, and revealing the path to extraordinary success